2020
DOI: 10.1186/s12889-020-09788-x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of sickness absence and disability pension in the year before and the three years following a bicycle crash; a nationwide longitudinal cohort study of 6353 injured individuals

Abstract: Background Bicyclists are the road user group with the highest number of severe injuries in the EU, yet little is known about sickness absence (SA) and disability pension (DP) following such injuries. Aims To explore long-term patterns of SA and DP among injured bicyclists, and to identify characteristics associated with the specific patterns. Methods A longitudinal register-based study was conducted, including all 6353 individuals aged 18–59 years and living in Sweden in 2009, who in 2010 had incident in-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…This could be seen in EU where pedestrians represent the road user group with the highest proportion of accidents where the injured is admitted to hospital and also the longest average of hospital stay [ 8 ]. Therefore, it should also be of interest to study the SA and DP of pedestrians in a longer perspective as have been done for bicycle crashes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be seen in EU where pedestrians represent the road user group with the highest proportion of accidents where the injured is admitted to hospital and also the longest average of hospital stay [ 8 ]. Therefore, it should also be of interest to study the SA and DP of pedestrians in a longer perspective as have been done for bicycle crashes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A modified version of the Barell matrix [ 15 ] was used to classify the ICD-10 codes into categories of type of injury and injured body region. Similar categorizations were used in recent studies on injuries among car occupants and bicyclists [ 16 – 19 ]. Type of injury was categorized into the following six groups: fracture; dislocation; sprains and strains; internal (brain, spinal cord, and other internal organs); external (open wounds, contusions, and superficial injuries) ( reference group ); and “other and unspecified”.…”
Section: Methodsmentioning
confidence: 99%
“…The type of injury was categorized into six groups: fracture; dislocation; sprains and strains; internal (brain, spinal cord, and other internal organs); external (open wounds, contusions, and superficial injuries) ( reference group ); and “other and unspecified”. Similar categorizations have been used in recent studies on injuries among different groups of road traffic users [ 8 , 12 – 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The sociodemographic factors were categorized as: sex (women; men ( reference group )), age group (20–24; 25–34 ( reference group ); 35–44; 45–54; 55–59 years), level of education (elementary school (≤ 9 years including missing); high school (9–12 years); university/college (> 12 years) ( reference group )), country of birth (Sweden ( reference group ); not Sweden), type of living area (cities ( reference group ); town and suburbs; rural areas), marital status (married ( reference group ); not married). These have all been demonstrated to be common risk factors for SA in general [ 16 ] and after a traffic related injury [ 8 , 12 – 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, although no consensus definition of sustainable working life exists [ 1 , 6 ], there is a need to understand various patterns of working life, with or without interruptions, over the life course. Until now, many earlier studies have focused on SA or DP due to specific diseases or conditions [ 7 , 8 , 9 , 10 ], but to the best of our knowledge, population-based cohort studies are rare for working life patterns identified via sequences with a long follow-up over the life course. Hence, a sequence analysis could provide assessment of the sustainable working life over time and informative clusters [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%